MEMBUMIKAN BUDAYA SUMATERA UTARA âBATAK JUGA PUNYA BATIKâ - Hartini, Titin; Kaban, Mhd. Agus Salim; Efendi, Riki (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Indonesia culture plagiarism by other country used to be a hot issue caused the culture it self has been a long time left or dissocialized in general public. One of the cultures that almost claimed by other country is Batik, but finally it got UNESCO recognition as Indonesia culture heritage. Program Kreativitas Mahasiswa (PKM) powered by DIKTI is one of a simple way to contribute in development and keeping the cultures of Indonesia, by following this program we are able to empower local potency art of culture and tourism in North Sumatera especially in form of batik, T-Shirt, and other batik product. Beside that,Â Â the effort of batik batak product become one of potential business opportunities for students either in doing the lectures or after graduation.Â Keywords: Culture, Batik, Business, PKM